Performance of the novel C-purlin tubular beams filled with recycled-lightweight concrete strengthened with CFRP sheet. (November 2021) - Al Zand, Ahmed W.; Hosseinpour, Emad; Badaruzzaman, Wan Hamidon W.; Ali, Mustafa M.; Yaseen, Zaher Mundher; Hanoon, Ammar N.
Abstract: This research investigates the performance of double C-purlin sections used in the concrete-filled steel tube (CFST) beams system. A recycled-lightweight concrete was used as infill material to reduce the newly suggested composite beam's self-weight and cost. Up to 70% of the raw coarse aggregate was replaced with the expanded polystyrene beads and recycled aggregate concrete. Also, the strengthening performance of the suggested CFST beam was investigated using carbon fiber reinforced polymer (CFRP) sheets. A total of seven specimens of concrete-filled C-purlin tubular sections were tested under four-point loads, and additional 12 models were numerically analyzed using finite element software. The conducted failure modes, flexural strength, flexural stiffness, and energy absorption index are presented and discussed. The results confirmed that the recycled-lightweight infill concrete material has a slightly lower influence on the investigated CFST beams' flexural performance than those with normal concrete (less than 10%). Like the conventional CFST beams, the double C-purlin tubular beams filled with recycled-lightweight concrete showed a normal response to the CFRP's strengthening quality. Moreover, the flexural strength capacity and stiffness values obtained from the current analyses are analogous with those theoretically predicted using the existing methods, which achieved mean values of about 0.759 and 1.126, respectively, as average prediction mean values of these methods. Graphical abstract: Image 1 Highlights: Investigate the flexural behavior of novel C-purlin tubular sections filled with recycled-lightweight concrete. Up to 70% of raw aggregate was replaced with recycled aggregate concrete materials. Confirmed that the C-purlin sections are applicable to use in the CFST beams system. The flexural strength/stiffness of the suggested CFST beams significantly improved by using CFRP sheets. The obtained experimental and numerical results are well verified by the existing methods.